CFTR POLYMORPHISMS OF HEALTHY INDIVIDUALS IN TWO CHINESE CITIES—CHANGCHUN AND NANJING - JIN, CHUN XIANG (Nagoya J Med Sci, 2012)
Background and Aim Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, which encodes a chloride channel, cause cystic fibrosis. In order to investigate the polymorphic backgrounds of CFTR genes of healthy populations in different Chinese cities (Changchun and Nanjing), we analyzed 119 blood samples (Changchun 64, Nanjing 55) of randomly selected healthy individuals for poly T, TG-repeats and M470V polymorphisms. We analyzed the differences of CFTR polymorphic distributions between the two Chinese cities from the south and the north. Methods Genomic DNA was extracted from whole blood. DNA fragments of CFTR gene were amplified by polymerase chain reaction (PCR). Poly-T and TG repeats were directly sequenced by auto sequencer (ABI 310). M470V was detected by a HphI restriction enzyme. Results The T7 allele was the most common haplotype in Changchun (0.938) and Nanjing (0.927) populations. The T5 allele was present in only 7 Changchun and 3 Nanjing subjects. The TG11 and TG12 alleles were dominant haplotypes in Changchun (TG11 0.500, TG12 0.453) and Nanjing (TG11 0.345, TG12 0.609). The frequency of the V470 allele was 0.633 in Changchun, which was higher than that in Nanjing (0.500) (p<0.05). There were three major haplotypes: T7-TG11-V470, T7-TG12-M470 and T7-TG12-V470. The T7-TG11-V470 was the most common haplotype in Changchun (0.514), while T7-TG12-M470 was the most common haplotype in Nanjing (0.500). Conclusion Though Changchun and Nanjing are in the same country, their polymorphic backgrounds of CFTR gene are very different. Most of the two populations have genotypes that cause lower CFTR function.